SKRINING DAN ISOLASI METABOLIT AKTIF ANTIBAKTERI KULTUR JAMUR ENDOFIT DARI TUMBUHAN Albertisia papuana Becc. [Screening and Isolation of Antibacterial Active Metabolite from the Culture of Endophytic Fungi from Albertisia papuana Becc.] - Fathoni, Ahmad; Ilyas, Muhammad; Cahyana, Antonius Herry; Agusta, Andria (BERITA BIOLOGI, 2013)
Totally 15 isolates of endophytic fungi were obtained from leaves and young stems of a medicinal plant Albertisia papuana Becc.(Menispermaceae). The antibacterial screening of the ethyl acetate extract derived from the fungi cultures in potato dextrose broth (PDB)were performed on a non eluted Thin Layer Chromatography Bioautography assay (TLC bioautography assay). From the screening test, itwas found that the ethyl acetate extract of the fungus Xylaria sp. DAP-KRI-5 culture showed strong antibacterial activity against Staphylococcus aureus. The isolation of active metabolite based on the bioautography guided assay from ethyl acetate extract of the Xylaria sp. DAP-KRI-5, led us to identify phloroglucinol as a main antibacterial compound. The chemical structure of phloroglucinol was deduced from it spectral data, including UV-Vis, 1H and 13C-NMR, GC-MS and published data elsewhere.